Functions of pipecolic acid on induced resistance against Botrytis cinerea and Pseudomonas syringae pv. tomato DC3000 in tomato plants. Issue 10 (7th August 2020) - Zhang, Huijuan; Qiu, Yating; Li, Miao; Song, Fengming; Jiang, Ming
Abstract: Amino acid metabolic pathways are involved in the plant immune system. Pipecolic acid (Pip), a lysine‐derived non‐protein amino acid, acts as an important regulator of disease resistance. Here, we report the functions of Pip on tomato disease resistance. Tomato seedlings treated with 0.5 mM Pip showed increased resistance to Pst DC3000 and B. cinerea compared with the control. After pathogen infection, the expression of defence‐related genes increased in plants pretreated with Pip, while reactive oxygen species (ROS) accumulation decreased. These data demonstrated that exogenous application of Pip induced resistance against Pst DC3000 and B. cinerea in tomatoes, possibly through the regulation of ROS accumulation and defence‐related gene expression.